Quantum-dot cellular automata based design of multifunction binary right shifter circuit. (July 2022) - Das, Jadav Chandra; De, Debashis
Highlights: The structure of a right shifter circuit to move one bit of an input message and its design in QCA. The structure of these proposed right shifter circuits has been reorganized to function as logical, arithmetic, and circular right shifters. Single-layer wire intersection has been utilized to give the most straightforward execution of the plans. Further, the proposed circuit is compared with other shifter circuits for better visualization of design complexities. Abstract: This article explores the basic design methodology of a 4-bit binary right shifter circuit and its implementation based on a QCA nano-device. The right shifter circuit can shift a single bit of an input message. The proposed shifter has been reorganized to function as a logical, arithmetic, and circular right shifter. Single-layer wire intersection has been utilized to give the most straightforward execution of the plans. These designs are helpful in floating-point handling frameworks, incredibly exceptionally valuable for the mantissa multiplication procedure. The design correctness is confirmed by contrasting hypothetical qualities and relating simulation results. The shifter consumes 435 QCA cells, 0.89µm 2 area with a latency of 1.75, and a circuit cost of 264.06. The design is compared with other shifters in terms of design complexities. The design has 0.628eV energy consumption at tunneling energy level 1.0Ek (kink energy). But it consumes only 0.190eV energy to perform multifunction shifting operations. Graphical abstract: Image, graphical abstract